Severe Fever with Thrombocytopenic Syndrome: Current Epidemiological Situation - E. I. Andaev; R. V. Adelshin; S. V. Balakhonov (Эпидемиология и вакцинопрофилактика)
Relevance. Severe fever with thrombocytopenia syndrome is a viral disease characterized by acute fever, accompanied by progressive thrombocytopenia, leucopenia. The mortality is up to 30%. The disease was first identified in 2009 in rural areas of central China, Hubei and Henan. The causative agent of the disease is a new Severe Fever with Thrombocytopenia Syndrome Virus (SFTSV). The SFTSV is mainly transmitted through tick bites, especially Haemaphysalis longicornis which is the dominant tick species in East Asia.The aim of the review is to analyze relevant information about Severe Fever with Thrombocytopenia Syndrome, including the molecular genetics features of the pathogen, clinical manifestations, geographical distribution, epidemiological features, as well as the possibility of drift and spread of infection in the Russian Federation.Conclusions. SFTS is a serious health threat as it relates to new and re-emerging infections. The further spread of SFTS in China may complicate the epidemiological situation in the country. SFTSV may have a much wider global distribution in Southeast Asia than is currently known. The risk of H. longicornis ticks spreading is predicted in the north-east United States, New Zealand, parts of Australia and several Pacific islands. The presence of the H. longicornis in the Primorsky Territory on the Far East indicates a possible risk of the natural focus formation in the event of the introduction of the pathogen.